Molecular breeding of farm animals through gene editing - Gao Fei; Hou Naipeng; Du Xuguang; Wang Yu; Zhao Jianguo; Wu Sen (National Science Open)
The rapid development of biotechnology has facilitated our understanding of the biological functions of candidate genes for important economic traits in farm animals. Molecular breeding by gene editing has greatly revolutionized the breeding of farm animals. Through gene editing and embryo manipulation, breeds with designed economic or disease-resistant traits can be readily generated. Along with this fast progress, the safety assessment of gene-edited farm animals has attracted public and regulatory attention. This review summarizes the research progress of gene editing in farm animals, focusing on performance improvement, disease resistance, bioreactors, animal welfare, and environmental friendliness. The limitations and future development of gene editing technology in farm animal breeding are also discussed.